High-temperature-resistant flame-retardant solid silica gel composition as well as preparation method and application thereof

By using homemade organically coated nanofillers and hollow multi-layer carbon microspheres/ionic liquid composites in silicone materials, combined with other ingredients, the problems of insufficient mechanical properties and lack of flame retardant properties of silicone materials at high temperatures are solved, and the problem of insufficient mechanical properties and lack of flame retardant properties of silicone materials at high temperatures is achieved. Excellent mechanical and flame retardant properties at high temperatures and improves edible oil resistance.

CN119505546AActive Publication Date: 2025-02-25DONGGUAN TIANAN SILICONES TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411690840.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing silicone materials lack mechanical properties under high temperature conditions and lack flame retardant properties, which cannot meet the needs of high-temperature kitchen appliances. The flame retardant used at the same time poses hidden dangers to human health.

Method used

Using homemade organically coated nanofillers and hollow multilayer carbon microspheres/ionic liquid composites, combined with methylvinyl silicone rubber raw rubber, hydroxy silicone oil and polytetrafluoroethylene ultrafine powder, prepared through specific ratios and processes A solid silicone composition that is resistant to high temperature and flame retardant is produced.

Benefits of technology

It has achieved excellent mechanical properties and flame retardant under high temperature conditions of 300°C, and at the same time it has improved the high-temperature edible oil resistance, avoiding the thermal degradation of solid silicone composition and edible oil corrosion at high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150895370000121
    Figure BDA0005150895370000121
Patent Text Reader

Abstract

The invention belongs to the technical field of silica gel, and particularly relates to a high-temperature-resistant flame-retardant solid silica gel composition as well as a preparation method and application thereof. The high-temperature-resistant flame-retardant solid silica gel composition is prepared from the following raw materials in parts by mass: 100 parts of methyl vinyl silicone rubber raw rubber, 20 to 30 parts of organic coated nano filler, 8 to 12 parts of flame retardant, 6 to 10 parts of hydroxyl silicone oil, 5 to 10 parts of polytetrafluoroethylene superfine powder, 3 to 8 parts of vulcanizing agent and 0.5 to 1.5 parts of release agent, the flame retardant is a hollow multilayer carbon microsphere / ionic liquid compound; the high-temperature-resistant flame-retardant solid silica gel composition provided by the invention has excellent high-temperature resistance, flame retardance and high-temperature edible oil resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone rubber, and in particular relates to a high-temperature resistant and flame-retardant solid silicone rubber composition and a preparation method and application thereof. Background Art

[0002] Silicone is widely used in household kitchen appliances due to its good electrical insulation properties. It can provide sealing, insulation and protection, thereby improving the performance and service life of household kitchen appliances. However, ordinary silicone has a low temperature resistance and cannot meet the needs of kitchen appliances such as microwave ovens, air fryers, ovens, etc. with a maximum temperature of 250°C or above.

[0003] In the prior art, a Chinese patent with publication number CN117106308A discloses a single-component dealcoholization type high temperature resistant silicone rubber for home appliance industry and its preparation method, which includes the following components: polyalkoxy-modified polymethyl (phenyl) silicone oil; heat resistant filler treated with polyalkoxy silicone oil; silicone resin; crosslinking agent; reinforcing filler; coupling agent; catalyst, which has the advantages of low odor, no corrosion, good adhesion, excellent high temperature resistance, dealcoholization type, and can meet the requirements of most home appliance high temperature resistant applications. However, the mechanical properties of the silicone rubber obtained by this technical solution need to be improved, and this technical solution does not pay attention to the flame retardant properties of silicone rubber.

[0004] The Chinese patent with publication number CN117447845A discloses a flame retardant and high temperature resistant silicone rubber and its production process. The composition comprises the following components by weight: (a) 90-100 parts of mixed raw rubber, (b) 3-5 parts of high vinyl silicone oil, (c) 0.5-1 part of tetrafluoroethylene powder, (d) 0.8-1.5 parts of methylphenyldiethoxysilane, (e) a high temperature resistant component, wherein the high temperature resistant component comprises the following: 0.05-0.2 parts of white carbon black and 3-5 parts of ferric oxide; (f) a flame retardant component, wherein the flame retardant component comprises the following: 4-10 parts of decabromodiphenyl ether and 5-8 parts of antimony pentoxide; (g) an auxiliary agent, wherein the auxiliary agent comprises 1-10 parts of a vulcanizing agent, 0.4-1 parts of a release agent and 0.5-5 parts of a catalyst; the weight of components (a)-(g) accounts for 90-100% of the total weight of the composition, calculated based on the total weight of the composition. The silicone rubber of this technical solution improves the proportion of raw material ingredients and production process, uses various automatic processing equipment to mix the raw materials of silicone rubber, simplifies its batching process, and improves its high temperature resistance and flame retardancy. However, the flame retardants decabromodiphenyl ether and antimony pentoxide used in this technical solution may cause harm to the human body, so there are hidden dangers when applied to household kitchen appliances. Summary of the invention

[0005] In view of the above problems, the present invention provides a high temperature resistant and flame retardant solid silicone composition and a preparation method and application thereof. The solid silicone composition of the present invention has excellent high temperature resistance, flame retardancy and high temperature edible oil resistance.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a high temperature resistant and flame retardant solid silicone composition, wherein the raw materials include, by weight: 100 parts of methyl vinyl silicone rubber, 20-30 parts of organically coated nanofiller, 8-12 parts of flame retardant, 6-10 parts of hydroxy silicone oil, 5-10 parts of polytetrafluoroethylene ultrafine powder, 3-8 parts of vulcanizing agent, and 0.5-1.5 parts of release agent;

[0008] The flame retardant is a hollow multilayer carbon microsphere / ionic liquid composite;

[0009] The nano filler is nano oxide loaded with amorphous silicon dioxide and hollow glass microspheres; the mass ratio of the nano oxide loaded with amorphous silicon dioxide to the hollow glass microspheres is (1-3): (0.5-1.5).

[0010] Preferably, the methyl vinyl silicone rubber raw rubber is vinyl terminated methyl vinyl silicone rubber raw rubber.

[0011] Preferably, the methyl vinyl silicone rubber raw rubber is a mixture of methyl vinyl silicone rubber raw rubber with a vinyl content of 0.21-0.24% and methyl vinyl silicone rubber raw rubber with a vinyl content of 4-5%; the mass ratio of the two is (4-6):1, preferably 5:1.

[0012] Preferably, the molecular weight of the methyl vinyl silicone rubber raw rubber with a vinyl content of 0.21-0.24% is 550,000-700,000, preferably 620,000±20,000.

[0013] Preferably, the molecular weight of the methyl vinyl silicone rubber with a vinyl content of 4-5% is 550,000-700,000, preferably 670,000±20,000.

[0014] Preferably, the hollow glass microspheres are of the C series produced by Zhongke Huaxing New Materials Co., Ltd., preferably model C100.

[0015] Preferably, the nano-oxides are nano-aluminum oxide, nano-silicon dioxide and nano-cerium dioxide; the mass ratio of the nano-aluminum oxide, nano-silicon dioxide and nano-cerium dioxide is (10-20): (10-20): (0.2-0.4), preferably 15:15:0.3.

[0016] Preferably, the method for preparing the organic-coated nanofiller comprises the following steps:

[0017] Step 1, adding ammonia water to the nano-oxide solution, adding ethyl orthosilicate at 30-40° C., stirring and reacting for 8-12 hours, centrifuging, washing and drying in sequence to obtain nano-oxide loaded with amorphous silicon dioxide;

[0018] Step 2, placing the hollow glass microspheres in a sodium hydroxide solution, refluxing and stirring at 70-90° C. for 1-2 hours, and washing and drying in sequence to obtain pretreated hollow glass microspheres;

[0019] Step 3: Place the nano-oxide loaded with amorphous silica and the pretreated hollow glass microspheres in a reaction kettle, add sodium hydride, stir and heat to 70-90° C. under nitrogen protection, slowly drop 4-vinylbenzyl glycidyl ether, and complete the addition within 1 hour. Continue to keep the temperature and stir for 6-8 hours, and cool down after the reaction is completed.

[0020] The inventor creatively adopts a self-made organically coated nanofiller, firstly loads amorphous silicon dioxide on the surface of nano oxide and pre-treats hollow glass microspheres with sodium hydroxide, the surfaces of amorphous silicon dioxide and hollow glass microspheres pre-treated with sodium hydroxide contain a large number of hydroxyl groups, so that 4-vinyl benzyl glycidyl ether can be coated on the surface with hydroxyl groups through a ring-opening reaction; the organically coated nanofiller not only has good compatibility in the methyl vinyl silicone rubber system, and enhances the interface strength between the nanofiller and the methyl vinyl silicone rubber, but also the benzene ring structure of 4-vinyl benzyl glycidyl ether not only improves the additional high temperature resistance, but also can form a carbon layer at high temperature, further improving its flame retardancy; at the same time The organic coating layer forms a protective film on the surface of the solid silica gel composition to reduce the erosion of the solid silica gel composition by edible oil; the hollow glass microspheres pretreated with sodium hydroxide become rough, which increases the contact area with the nano oxides and makes them stacked more closely; the nano alumina, nano silica and nano cerium dioxide in the nano oxides work together to reduce the oxidation reaction of the solid silica gel composition at high temperature and reduce thermal degradation; through the joint action of the nano oxides, the hollow glass microspheres and 4-vinyl benzyl glycidyl ether, the high temperature resistant and flame retardant solid silica gel composition of the present invention can not only have excellent mechanical properties under high temperature conditions of 300°C, but also have good flame retardancy and high temperature edible oil resistance.

[0021] Preferably, the nano-oxide solution is prepared by dispersing 40-60 mg of nano-oxide in 100 mL of ethanol aqueous solution.

[0022] Preferably, the ethanol aqueous solution consists of ethanol and water in a mass ratio of 90-95:5-10.

[0023] Preferably, the volume ratio of the nano-oxide aqueous solution, ammonia water and tetraethyl orthosilicate is 100:(3-5):(5-6).

[0024] Preferably, the mass fraction of the ammonia water is 25%.

[0025] Preferably, the mass volume ratio of the hollow glass microspheres to the sodium hydroxide solution is (0.02-0.04) g:1 mL.

[0026] Preferably, the concentration of the sodium hydroxide solution is 0.3-0.5 mol / L.

[0027] Preferably, the amount of sodium hydride added is 0.2-0.5% of the total mass of the nano-oxide loaded with amorphous silicon dioxide and the hollow glass microspheres.

[0028] Preferably, the amount of 4-vinylbenzyl glycidyl ether added is 55-65% of the total mass of the amorphous silicon dioxide-loaded nano-oxide and the hollow glass microspheres.

[0029] Preferably, the method for preparing the hollow multilayer carbon microsphere / ionic liquid composite comprises the following steps:

[0030] S1, mixing melamine solution and cyanuric acid solution evenly, reacting at 25-35°C for 20-30min, centrifuging, washing and drying in sequence to obtain melamine cyanuric acid composite microspheres;

[0031] S2, mixing the melamine cyanuric acid composite microsphere solution and the dopamine solution evenly, stirring at 25-35° C. for 20-40 min, adding Tris buffer, reacting at 25-35° C. for 10-15 h, centrifuging, washing and drying in sequence to obtain polydopamine-coated melamine cyanuric acid composite microspheres;

[0032] S3, in an inert atmosphere, heat the polydopamine-coated melamine-cyanuric acid composite microspheres at 400-500° C. for 2-3 h, and then heat at 750-850° C. for 2-3 h to obtain hollow multilayer carbon microspheres;

[0033] S4. Place the hollow multilayer carbon microspheres in a vacuum environment, add ionic liquid dropwise, and wash and dry in sequence after the addition is completed.

[0034] The inventor creatively adopts a self-made hollow multilayer carbon microsphere / ionic liquid composite, first prepares melamine cyanuric acid composite microspheres, then coats them with polydopamine, and then calcines them to obtain hollow multilayer carbon microspheres, and finally the ionic liquid can be adsorbed inside and on the surface of the hollow multilayer carbon microspheres; the hollow multilayer carbon microspheres form a stable carbon layer at high temperature, isolate oxygen and heat, effectively inhibit the spread of flames, and at the same time, the flame retardant elements in the ionic liquid avoid further oxidation of the carbon layer, thereby having excellent flame retardant properties, and at the same time, the hollow structure and multilayer structure of the hollow multilayer carbon microspheres have a large specific surface area, have a strong interface effect with methyl vinyl silicone rubber, and have excellent high thermal stability; through the joint action of the hollow multilayer carbon microspheres and the ionic liquid, the high temperature resistant and flame retardant solid silicone composition of the present invention has excellent flame retardancy and improved high temperature resistance.

[0035] Preferably, the melamine solution is prepared by dissolving 0.4-0.6 g of melamine in 15-20 mL of dimethyl sulfoxide.

[0036] Preferably, the preparation method of the cyanuric acid solution is: dissolving 0.4-0.6 g of cyanuric acid in 5-15 mL of dimethyl sulfoxide.

[0037] Preferably, the volume ratio of the melamine solution to the cyanuric acid solution is (1.5-2):1.

[0038] Preferably, the preparation method of the melamine cyanuric acid composite microsphere solution is: 0.4-0.6g of melamine cyanuric acid composite microspheres are dissolved in 100mL of water.

[0039] Preferably, the dopamine solution is prepared by dissolving 0.4-0.6 g of dopamine hydrochloride in 100 mL of water.

[0040] Preferably, the preparation method of the Tris buffer is as follows: 0.4-0.6 g of tris(hydroxymethyl)aminomethane is dissolved in 100 mL of water.

[0041] Preferably, the volume ratio of the melamine cyanuric acid composite microsphere solution, the dopamine solution and the Tris buffer is 1:1:1.

[0042] Preferably, the mass ratio of the hollow multilayer carbon microspheres to the ionic liquid is 1:(30-40).

[0043] Preferably, the ionic liquid comprises 1-ethyl acetate-3-methylimidazolium hexafluorophosphate and / or 1-ethyl acetate-3-methylimidazolium tetrafluoroborate.

[0044] Preferably, the hydroxyl content of the hydroxy silicone oil is 8-10wt% and the viscosity is 30-35mm2 / s, preferably, the hydroxyl content of the hydroxy silicone oil is 9wt% and the viscosity is 30mm 2 / s.

[0045] Preferably, the polytetrafluoroethylene ultrafine powder includes polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<5.0μm, D90<10μm and polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11μm, D90<15μm; the mass ratio of the two is (2-4):1.

[0046] Preferably, the mass ratio of the organic-coated nanofiller, the flame retardant and the polytetrafluoroethylene powder is (2.2-2.8):1:0.8, preferably 2.5:1:0.8.

[0047] Kitchen appliances are often inevitably exposed to edible oil. The inventors have found that the solid silicone composition has poor edible oil resistance at high temperatures only through the effects of organically coated nanofillers and hollow multilayer carbon microspheres / ionic liquid composites. To solve this technical problem, the inventors unexpectedly found that compared with polytetrafluoroethylene superfine powder with a single particle size distribution, the solid silicone composition has better edible oil resistance at 300°C by using polytetrafluoroethylene superfine powder with a particle size distribution of D50<5.0μm, D90<10μm and polytetrafluoroethylene superfine powder with a particle size distribution of D50<11μm, D90<15μm, and further improves its mechanical properties at 300°C. The inventors speculate that this is because the two types of polytetrafluoroethylene ultrafine powders with different particle size distributions can not only better fill the tiny pores in the methyl vinyl silicone rubber, but also can be adsorbed at different positions of the hollow multilayer carbon microspheres to form a multi-level oleophobic structure, thereby being able to avoid edible oil penetration at a high temperature of 300°C while avoiding thermal degradation of the solid silicone composition; and the inventors also found that when the mass ratio of the organic-coated nanofiller, the flame retardant and the polytetrafluoroethylene powder is not in the range of (2.2-2.8):1:0.8, the mechanical properties at 300°C and the edible oil resistance at 300°C of the solid silicone composition decrease.

[0048] Preferably, the vulcanizing agent is selected from at least one of di-tert-butyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide and tert-butyl perbenzoate.

[0049] Preferably, the release agent is selected from at least one of stearic acid, zinc stearate, calcium stearate, magnesium stearate and aluminum stearate.

[0050] The second aspect of the present invention provides a method for preparing the above-mentioned high temperature resistant and flame retardant solid silicone composition, comprising the following steps: firstly placing methyl vinyl silicone rubber raw rubber in an open mill for mixing, then adding organically coated nanofiller, flame retardant, hydroxy silicone oil, polytetrafluoroethylene ultrafine powder, and release agent for mixing, and finally adding a vulcanizing agent for mixing to obtain.

[0051] Preferably, the preparation method of the high temperature resistant and flame retardant solid silicone composition comprises the following steps: firstly placing the methyl vinyl silicone rubber raw rubber in an open mill, mixing it at 30-40°C for 20-30min, then adding the organically coated nanofiller, flame retardant, hydroxy silicone oil, polytetrafluoroethylene ultrafine powder, and release agent and continuing to mix it for 5-15min, leaving it for 12h, and finally adding the vulcanizing agent and mixing it evenly.

[0052] The third aspect of the present invention provides the use of the above-mentioned high temperature resistant and flame retardant solid silicone composition in the preparation of a high temperature resistant and flame retardant sealing material.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] 1. The present invention creatively adopts self-made organic-coated nanofillers, so that the high-temperature resistant and flame-retardant solid silicone composition not only has excellent mechanical properties under high temperature conditions of 300°C, but also has good flame retardancy and edible oil resistance.

[0055] 2. The present invention creatively adopts a self-made hollow multilayer carbon microsphere / ionic liquid composite, so that the high temperature resistant and flame retardant solid silicone composition has excellent flame retardancy while also improving high temperature resistance.

[0056] 3. The present invention uses polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<5.0μm, D90<10μm and polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11μm, D90<15μm, so that the solid silica gel composition has more excellent edible oil resistance at a high temperature of 300°C, and further improves its mechanical properties at a high temperature of 300°C.

[0057] 4. The inventors controlled the mass ratio of the organically coated nanofiller, the flame retardant and the polytetrafluoroethylene powder to be (2.2-2.8):1:0.8, thereby avoiding the decrease in the mechanical properties of the solid silica gel composition at 300°C and the edible oil resistance at 300°C. DETAILED DESCRIPTION

[0058] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.

[0059] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0060] In the following examples and comparative examples, unless otherwise specified, all raw materials used were commercially available or prepared by conventional methods in the art.

[0061] Example 1

[0062] The high temperature resistant and flame retardant solid silicone composition comprises, by weight, 100 parts of methyl vinyl silicone rubber, 20 parts of organically coated nanofiller, 8 parts of flame retardant, 6 parts of hydroxy silicone oil, 5 parts of polytetrafluoroethylene ultrafine powder, 3 parts of vulcanizing agent and 0.5 parts of release agent.

[0063] The methyl vinyl silicone rubber raw rubber is vinyl-terminated methyl vinyl silicone rubber raw rubber, and the methyl vinyl silicone rubber raw rubber is a mixture of methyl vinyl silicone rubber raw rubber with a vinyl content of 0.21-0.24% and methyl vinyl silicone rubber raw rubber with a vinyl content of 4-5%, and the mass ratio of the two is 5:1.

[0064] The molecular weight of the methyl vinyl silicone rubber raw rubber with a vinyl content of 0.21-0.24% is 620,000±20,000 and is purchased from Dongjue Silicone Group Co., Ltd., model 110-3.

[0065] The molecular weight of the methyl vinyl silicone rubber raw rubber with a vinyl content of 4-5% is 67±20,000 and is purchased from Dongjue Silicone Group Co., Ltd., model 110-7.

[0066] The nano filler is nano oxide loaded with amorphous silicon dioxide and hollow glass micro beads; the mass ratio of the nano oxide loaded with amorphous silicon dioxide to the hollow glass micro beads is 2:1.

[0067] The hollow glass microspheres are hollow glass microspheres produced by Zhongke Huaxing New Materials Co., Ltd., model C100.

[0068] The nano-oxides are nano-alumina, nano-silicon dioxide and nano-cerium dioxide; the mass ratio of the nano-oxides is 15:15:0.3.

[0069] The particle size of the nano-alumina is 30 nm, and it was purchased from Beijing Zhongke Jinyan Technology Co., Ltd., model: DK-Al2O3-A30.

[0070] The nano-silicon dioxide has a particle size of 15 nm and is purchased from Beijing Zhongke Jinyan Technology Co., Ltd., model: DK-SiO2-15.

[0071] The particle size of the nano-cerium dioxide is 20 nm, and it was purchased from Beijing Zhongke Jinyan Technology Co., Ltd., model: DK-SiO2-15.

[0072] The method for preparing the organically coated nanofiller comprises the following steps:

[0073] Step 1, adding ammonia water to the nano-oxide solution, adding tetraethyl orthosilicate (CAS No.: 78-10-4) at 35° C., stirring and reacting for 10 hours, centrifuging, washing and drying in sequence to obtain nano-oxide loaded with amorphous silicon dioxide;

[0074] Step 2, placing the hollow glass microspheres in a sodium hydroxide solution, refluxing and stirring at 80° C. for 1.5 h, and washing and drying in sequence to obtain pretreated hollow glass microspheres;

[0075] Step 3: Place the nano-oxide loaded with amorphous silica and the pretreated hollow glass microspheres in a reaction kettle, add sodium hydride, stir and heat to 80°C under nitrogen protection, slowly add 4-vinylbenzyl glycidyl ether (CAS No.: 113538-80-0) dropwise, and complete the addition within 1 hour. Continue to keep the temperature and stir the reaction for 7 hours, and cool down after the reaction is completed.

[0076] The preparation method of the nano oxide solution is: dispersing 50 mg of nano oxide in 100 mL of ethanol aqueous solution; the ethanol aqueous solution is composed of ethanol and water in a mass ratio of 94:6.

[0077] The volume ratio of the nano-oxide aqueous solution, ammonia water and tetraethyl orthosilicate is 100:4:4.5; the mass fraction of the ammonia water is 25%.

[0078] The mass volume ratio of the hollow glass microspheres to the sodium hydroxide solution is 0.03 g:1 mL; the concentration of the sodium hydroxide solution is 0.4 mol / L.

[0079] The amount of sodium hydride added is 0.4% of the total mass of the nano-oxide loaded with amorphous silicon dioxide and the hollow glass microspheres.

[0080] The added amount of the 4-vinylbenzyl glycidyl ether is 60% of the total mass of the nano-oxide loaded with amorphous silicon dioxide and the hollow glass microspheres.

[0081] The flame retardant is a hollow multilayer carbon microsphere / ionic liquid composite; the preparation method of the hollow multilayer carbon microsphere / ionic liquid composite comprises the following steps:

[0082] S1, mixing melamine solution and cyanuric acid solution evenly, reacting at 30°C for 25 minutes, centrifuging, washing and drying in sequence to obtain melamine cyanuric acid composite microspheres;

[0083] S2, mixing the melamine cyanuric acid composite microsphere solution and the dopamine solution evenly, stirring at 30°C for 30 minutes, adding Tris buffer, reacting at 30°C for 12 hours, centrifuging, washing and drying in sequence to obtain polydopamine-coated melamine cyanuric acid composite microspheres;

[0084] S3, keeping the polydopamine-coated melamine-cyanuric acid composite microspheres in an inert atmosphere at 450° C. for 2.5 h, and then keeping them at 800° C. for 2.5 h, to obtain hollow multilayer carbon microspheres;

[0085] S4. Place the hollow multilayer carbon microspheres in a vacuum environment, add ionic liquid dropwise, and wash and dry in sequence after the addition is completed.

[0086] The preparation method of the melamine solution is as follows: 0.5 g of melamine (CAS No.: 108-78-1) is dissolved in 18 mL of dimethyl sulfoxide (CAS No.: 67-68-5).

[0087] The preparation method of the cyanuric acid solution is as follows: 0.5 g of cyanuric acid (CAS No.: 108-80-5) is dissolved in 12 mL of dimethyl sulfoxide.

[0088] The volume ratio of the melamine solution to the cyanuric acid solution is 1.8:1.

[0089] The preparation method of the melamine cyanuric acid composite microsphere solution is as follows: 0.5 g of melamine cyanuric acid composite microsphere is dissolved in 100 mL of water.

[0090] The preparation method of the dopamine solution is as follows: 0.5 g of dopamine hydrochloride (CAS No.: 62-31-7) is dissolved in 100 mL of water.

[0091] The preparation method of the Tris buffer is as follows: 0.5 g of tris(hydroxymethyl)aminomethane (CAS No.: 77-86-1) is dissolved in 100 mL of water.

[0092] The volume ratio of the melamine cyanuric acid composite microsphere solution, the dopamine solution and the Tris buffer solution is 1:1:1.

[0093] The mass ratio of the hollow multilayer carbon microspheres to the ionic liquid is 1:35.

[0094] The ionic liquid is 1-ethyl acetate-3-methylimidazolium hexafluorophosphate, which was purchased from Xi'an Qiyue Biotechnology Co., Ltd.

[0095] The hydroxyl content of the hydroxy silicone oil is 9wt% and the viscosity is 30mm 2 / s, purchased from Zhejiang Zhenghe Silicon Materials Co., Ltd., brand: 207-30.

[0096] The polytetrafluoroethylene ultrafine powder includes polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<5.0μm, D90<10μm and polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11μm, D90<15μm; the mass ratio of the two is 3:1; both are purchased from Fuzhou Taipuda New Materials Co., Ltd., and the models are TPD-505 and TPD-511 respectively.

[0097] The vulcanizing agent is di-tert-butyl peroxide (CAS No.: 110-05-4).

[0098] The release agent is magnesium stearate (CAS No.: 557-04-0).

[0099] The preparation method of the above-mentioned high-temperature resistant and flame-retardant solid silicone rubber composition comprises the following steps: firstly placing the methyl vinyl silicone rubber raw rubber in an open mill and mixing it at 35°C for 25 minutes, then adding organically coated nanofiller, flame retardant, hydroxy silicone oil, polytetrafluoroethylene ultrafine powder, and release agent and continuing to mix for 10 minutes, leaving it for 12 hours, and finally adding a vulcanizing agent and mixing it evenly.

[0100] Example 2

[0101] The difference from Example 1 is that the high temperature resistant and flame retardant solid silicone composition, calculated by mass, includes the following raw materials: 100 parts of methyl vinyl silicone rubber, 30 parts of organically coated nanofiller, 12 parts of flame retardant, 10 parts of hydroxy silicone oil, 10 parts of polytetrafluoroethylene ultrafine powder, 8 parts of vulcanizing agent, and 1.5 parts of release agent; the rest are the same.

[0102] The preparation method of the above-mentioned high temperature resistant and flame retardant solid silicone composition is the same as that of Example 1.

[0103] Example 3

[0104] The difference from Example 1 is that the high temperature resistant and flame retardant solid silicone composition, calculated by mass, includes the following raw materials: 100 parts of methyl vinyl silicone rubber, 25 parts of organically coated nanofiller, 10 parts of flame retardant, 8 parts of hydroxy silicone oil, 8 parts of polytetrafluoroethylene ultrafine powder, 5 parts of vulcanizing agent, and 1 part of release agent; the rest are the same.

[0105] The preparation method of the above-mentioned high temperature resistant and flame retardant solid silicone composition is the same as that of Example 1.

[0106] Comparative Example 1

[0107] The difference from Example 3 is that the organic-coated nanofiller is replaced with a nanofiller of the same mass; the rest is the same.

[0108] Comparative Example 2

[0109] The difference from Example 3 is that the hollow glass microspheres are replaced with an equal mass of nano-oxide loaded with amorphous silicon dioxide; the rest are the same.

[0110] Comparative Example 3

[0111] The difference from Example 3 is that the hollow glass microspheres are replaced with nano-cerium dioxide of the same mass; the rest are the same.

[0112] Comparative Example 4

[0113] The difference from Example 3 is that the hollow multilayer carbon microsphere / ionic liquid composite is replaced with hollow multilayer carbon microspheres of equal mass; the rest are the same.

[0114] Comparative Example 5

[0115] The difference from Example 3 is that the hollow multilayer carbon microsphere / ionic liquid composite is replaced with an ionic liquid of the same mass; the rest is the same.

[0116] Comparative Example 6

[0117] The difference from Example 3 is that the hollow multilayer carbon microsphere / ionic liquid composite is replaced by a hollow carbon microsphere / ionic liquid composite of equal mass; the preparation method of the hollow carbon microsphere / ionic liquid composite comprises the following steps:

[0118] S1, mixing melamine solution and cyanuric acid solution evenly, reacting at 30°C for 25 minutes, centrifuging, washing and drying in sequence to obtain melamine cyanuric acid composite microspheres;

[0119] S3, keeping the melamine-cyanuric acid composite microspheres in an inert atmosphere at 450° C. for 2.5 h, and then keeping them at 800° C. for 2.5 h, to obtain hollow carbon microspheres;

[0120] S3, placing the hollow carbon microspheres in a vacuum environment, adding ionic liquid dropwise, and washing and drying in sequence after the addition is completed; the rest are the same.

[0121] Comparative Example 7

[0122] The difference from Example 3 is that the polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11 μm, D90<15 μm is replaced by polytetrafluoroethylene ultrafine powder of the same mass with a particle size distribution of D50<5.0 μm, D90<10 μm; the rest are the same.

[0123] Comparative Example 8

[0124] The difference from Example 3 is that the mass ratio of the organically coated nanofiller, flame retardant and polytetrafluoroethylene powder is 2:1.3:1, that is, the high temperature resistant and flame retardant solid silicone composition, the raw materials include, by mass: 100 parts of methyl vinyl silicone rubber, 20 parts of organically coated nanofiller, 13 parts of flame retardant, 8 parts of hydroxy silicone oil, 10 parts of polytetrafluoroethylene ultrafine powder, 5 parts of vulcanizing agent, and 1 part of release agent; the rest are the same.

[0125] Performance Test:

[0126] The high temperature resistant and flame retardant solid silicone compositions of Examples 1-3 and Comparative Examples 1-8 were respectively placed in a flat vulcanizer for vulcanization, specifically: firstly, a first stage of vulcanization was performed: the vulcanization temperature was 120°C, the vulcanization pressure was 15MPa, and the vulcanization time was 30min; then, a second stage of vulcanization was performed: the vulcanization temperature was 200°C, and the vulcanization time was 3h; and the following performance tests were performed on the vulcanized molded samples:

[0127] 1. Tensile strength: Test standard: GB / T528-2009;

[0128] 2. Elongation at break: Test standard: GB / T528-2009;

[0129] 3. Flame retardancy: test standard: UL94;

[0130] 4. High temperature resistance: test standard GB / T3512-2004;

[0131] 5. Edible oil resistance: Corn oil was coated on the high temperature resistant and flame retardant solid silicone composition, and then tested according to the standard GB / T3512-2004.

[0132] The results are shown in Table 1:

[0133] Table 1 Performance test results of high temperature resistant and flame retardant solid silicone compositions of Examples 1-3 and Comparative Examples 1-8

[0134]

[0135] It can be seen from Table 1 that the high temperature resistant flame retardant solid silica gel combination of Examples 1-3 has excellent mechanical properties regardless of aging at 300°C for 8 days or aging at 300°C for 8 days after being coated with edible oil, and the flame retardant level is V0;

[0136] In Comparative Example 1, the organically coated nanofiller is replaced with a nanofiller of equal mass; in Comparative Example 2, the hollow glass microspheres are replaced with a nano-oxide loaded with amorphous silicon dioxide of equal mass; in Comparative Example 3, the hollow glass microspheres are replaced with nano-cerium dioxide of equal mass; that is, Comparative Examples 1-3 change the composition of the organically coated nanofiller, and the mechanical properties of the obtained high temperature resistant flame retardant solid silica gel composition after aging at 300° C. for 8 days and after aging at 300° C. for 8 days after coating with edible oil are both reduced, and the flame retardant grade of Comparative Examples 1-2 is also reduced;

[0137] In Comparative Example 4, the hollow multilayer carbon microsphere / ionic liquid composite was replaced with an equal mass of hollow multilayer carbon microspheres; in Comparative Example 5, the hollow multilayer carbon microsphere / ionic liquid composite was replaced with an equal mass of ionic liquids; in Comparative Example 6, the hollow multilayer carbon microsphere / ionic liquid composite was replaced with an equal mass of hollow carbon microsphere / ionic liquid composite; that is, Comparative Examples 4-6 changed the composition of the hollow multilayer carbon microsphere / ionic liquid composite, and the flame retardant properties of the obtained high temperature resistant flame retardant solid silicone composition were significantly reduced, and the mechanical properties after aging at 300°C for 8 days and aging at 300°C for 8 days after coating with edible oil were also reduced;

[0138] Comparative Example 7: The polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11μm and D90<15μm was replaced with polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<5.0μm and D90<10μm of the same mass; the mechanical properties of the obtained high temperature resistant flame retardant solid silica gel combination after aging at 300°C for 8 days after coating with edible oil were significantly reduced; and the mechanical properties of the obtained high temperature resistant flame retardant solid silica gel combination after aging at 300°C for 8 days were also reduced;

[0139] In Comparative Example 8, the mass ratio of the organically coated nanofiller, the flame retardant and the polytetrafluoroethylene powder is not within the range of (2.2-2.8):1:0.8, and the mechanical properties of the high temperature resistant flame retardant solid silicone composition after aging at 300°C for 8 days and the mechanical properties of the composition after aging at 300°C for 8 days after being coated with edible oil are both reduced.

[0140] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A high temperature resistant and flame retardant solid silicone composition, characterized in that: The raw materials include, by weight: 100 parts of methyl vinyl silicone rubber, 20-30 parts of organically coated nanofiller, 8-12 parts of flame retardant, 6-10 parts of hydroxy silicone oil, 5-10 parts of polytetrafluoroethylene ultrafine powder, 3-8 parts of vulcanizing agent, and 0.5-1.5 parts of release agent; The flame retardant is a hollow multilayer carbon microsphere / ionic liquid composite; The nano filler is nano oxide loaded with amorphous silicon dioxide and hollow glass microspheres; the mass ratio of the nano oxide loaded with amorphous silicon dioxide to the hollow glass microspheres is (1-3): (0.5-1.5).

2. The high temperature resistant and flame retardant solid silicone composition according to claim 1, characterized in that: The methyl vinyl silicone rubber raw rubber is a mixture of methyl vinyl silicone rubber raw rubber with a vinyl content of 0.21-0.24% and methyl vinyl silicone rubber raw rubber with a vinyl content of 4-5%, and the mass ratio of the two is (4-6):

1.

3. The high temperature resistant and flame retardant solid silicone composition according to claim 1, characterized in that: The nano-oxides are nano-aluminum oxide, nano-silicon dioxide and nano-cerium dioxide; the mass ratio of the nano-aluminum oxide, nano-silicon dioxide and nano-cerium dioxide is (10-20): (10-20): (0.2-0.4).

4. The high temperature resistant and flame retardant solid silicone composition according to claim 3, characterized in that: The method for preparing the organically coated nanofiller comprises the following steps: Step 1, adding ammonia water to the nano-oxide solution, adding ethyl orthosilicate at 30-40° C., stirring and reacting for 8-12 hours, centrifuging, washing and drying in sequence to obtain nano-oxide loaded with amorphous silicon dioxide; Step 2, placing the hollow glass microspheres in a sodium hydroxide solution, refluxing and stirring at 70-90° C. for 1-2 hours, and washing and drying in sequence to obtain pretreated hollow glass microspheres; Step 3: Place the nano-oxide loaded with amorphous silica and the pretreated hollow glass microspheres in a reaction kettle, add sodium hydride, stir and heat to 70-90° C. under nitrogen protection, slowly drop 4-vinylbenzyl glycidyl ether, and complete the addition within 1 hour. Continue to keep the temperature and stir for 6-8 hours, and cool down after the reaction is completed.

5. The high temperature resistant and flame retardant solid silicone composition according to claim 1, characterized in that: The method for preparing the hollow multilayer carbon microsphere / ionic liquid composite comprises the following steps: S1, mixing melamine solution and cyanuric acid solution evenly, reacting at 25-35°C for 20-30min, centrifuging, washing and drying in sequence to obtain melamine cyanuric acid composite microspheres; S2, mixing the melamine cyanuric acid composite microsphere solution and the dopamine solution evenly, stirring at 25-35° C. for 20-40 min, adding Tris buffer, reacting at 25-35° C. for 10-15 h, centrifuging, washing and drying in sequence to obtain polydopamine-coated melamine cyanuric acid composite microspheres; S3, in an inert atmosphere, heat the polydopamine-coated melamine-cyanuric acid composite microspheres at 400-500° C. for 2-3 h, and then heat at 750-850° C. for 2-3 h to obtain hollow multilayer carbon microspheres; S4. Place the hollow multilayer carbon microspheres in a vacuum environment, add ionic liquid dropwise, and wash and dry in sequence after the addition is completed.

6. The high temperature resistant and flame retardant solid silicone composition according to claim 5, characterized in that: The ionic liquid includes 1-ethyl acetate-3-methylimidazolium hexafluorophosphate and / or 1-ethyl acetate-3-methylimidazolium tetrafluoroborate.

7. The high temperature resistant and flame retardant solid silicone composition according to claim 1, characterized in that: The polytetrafluoroethylene ultrafine powder includes polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<5.0μm and D90<10μm and polytetrafluoroethylene ultrafine powder with a particle size distribution of D50<11μm and D90<15μm; the mass ratio of the two is (2-4):

1.

8. The high temperature resistant and flame retardant solid silicone composition according to any one of claims 1 to 7, characterized in that: The mass ratio of the organically coated nano filler, the flame retardant and the polytetrafluoroethylene powder is (2.2-2.8):1:0.

8.

9. The method for preparing the high temperature resistant and flame retardant solid silicone composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: Firstly, the raw methyl vinyl silicone rubber is placed in an open mill for mixing, then the organic coated nano filler, flame retardant, hydroxy silicone oil, polytetrafluoroethylene ultrafine powder and release agent are added for mixing, and finally the vulcanizing agent is added for mixing to obtain the product.

10. Use of the high temperature resistant and flame retardant solid silicone composition according to any one of claims 1 to 8 in the preparation of high temperature resistant and flame retardant sealing materials.

Citation Information

Patent Citations

  • Single-component dealcoholized high-temperature-resistant silicone rubber for household appliance industry and preparation method thereof

    CN117106308A

  • High-strength high-temperature-resistant flame-retardant silicone rubber and preparation method thereof

    CN111004511A

  • High-temperature-resistant halogen-free flame-retardant environment-friendly cable for intelligent energy motor train unit and production process

    CN112037984A

  • Flame-retardant high-temperature-resistant silicone rubber and production process thereof

    CN117447845A

  • High-temperature-resistant and edible-oil-resistant silicone rubber and preparation method thereof

    CN117801542A